An Introduction to the Septal Extension Graft - Myung-Hoon Kim (Archives of Plastic Surgery, 2014)
The septal extension graft is a very useful method of controlling nasal lengthening and tip projection, rotation, and shape by fixing a graft to the septum, which leads to a strong supporting structure. Enhancing graft stability is important for better long-term outcomes and minimizing complications or relapse, and even more efficient application of these methods is needed for East Asians who lack enough cartilage to be harvested in addition to possessing a weak cartilage framework. In this paper, the methods for overcoming the drawbacks of the septal extension graft, such as instability, a fixed tip, and insufficiency of cartilage, are presented, and the applications of each method for greater satisfaction with surgical outcomes are also discussed.